THE IMPACT OF GREEN MARKETING TOOLS ON CONSUMER BEHAVIOR IN THE CONTEXT OF EU GREEN TRANSITION - TARANENKO, Iryna; MOSTOVA, Anastasia; SHCHOLOKOVA, Hanna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Green marketing is an important component part of the development and implementation of consumption and production models aimed at achieving sustainable development goals. A key factor contributing to the green transition is the ability of green marketing to influence consumer behavior. The article considers the specific features of implementation the green marketing tools in the context of the European Green Deal and Green Transition in the European Union. The purpose of the study is to determine the impact of green marketing tools on consumer behavior and to find out the possibilities of implementing green marketing for businesses and consumers. It is shown that green marketing aligns the business goals of enterprises with the goals of sustainable development, contributing to the formation of long-term value for business and society. The following challenges related to the introduction of green marketing in the EU have been identified: skepticism of consumers related to companies’ statements about the environmental friendliness of their products; sensitivity of the mass consumer to price and frequent reluctance to overpay for "green" brands and environmentally friendly products; spreading misleading claims by companies about the environmental benefits of the product; difficulties for businesses, which creates EU regulations, including environmental compliance costs and administrative burdens. Summarizing and analyzing the results of a survey conducted in 2023 in 27 EU countries as part of the Eurobarometer project, aimed at finding out citizens’ awareness and attitudes to the EU ecolabel, allowed the authors to identify the specific features of the impact of green marketing tools, and in particular the EU ecolabel, on consumer behavior and identify opportunities for effective implementation of green marketing.